Desempenho e comportamento ingestivo de novilhos de corte confinados alimentados com diferentes proporções de silagem de girassol (Helianthus annuus l.) na dieta - Freitas, Leandro da Silva (2008)
The objective of the present study was to evaluate the effect of diet substitution of maize silage by sunflower silage on performance and ingestive behavior of feedlot steers. Nine steers, with average initial live weight and age of 288 kg and 20 months, respectively, from Nellore (N), 21/32Charolais (C) 11/32N and 21/32N 11/32C genetic groups, were used. The tested diets were: SG0= roughage with 100% of maize silage and 0% of sunflower silage; SG33= roughage with 67% of maize silage and 33% of sunflower silage and SG66= roughage of 34% of maize silage and 66% of sunflower silage. For all diets, the roughage:concentrate ratio used was of 60:40. The substitution of maize silage by sunflower silage didn t influence (P>.05) dry matter, neutral and acid detergent fiber and digestible energy intakes. A significant difference (P<.05) was observed for ether extract, being the higher value for SG66 (.83kg/day), the intermediary for SG33 (.63 kg/day) and the lower for SG0 (.50 kg/day). The slaughter weight, average daily weight gain, final body condition, feed and energetic conversions weren t influenced (P>.05) by treatments. Steers fed with SG66 stayed more time ruminating (P<.05) in relation to SG33 and SG0 animals, being values of 9.45; 8.76 and 8.61 h, respectively for SG66; SG33 and SG0. Animals fed with SG0 presented better (P<.05) dry matter and detergent fiber rumination. The time spending with feeding was higher (P<.05) for SG0 (32.58 min), intermediary for SG33 (28.33 min) and lower for SG66 (23.46 min).